Gender role differentiation in household fuel transition decision-making: Implications for education and training in Uganda - Elasu, Joseph; Ntayi, Joseph Mpeera; Adaramola, Muyiwa S.; Buyinza, Faisal; Ngoma, Muhammad; Atukunda, Ronnette (Frontiers in Sustainability, 2023)
Abstract: The role of gender and gender differences has been of long standing interest and has remained a concern regarding the access and use of energy fuels for cooking in households. Whereas there seems to be a thin line between gender differences and gender, the latter refers to the socially constructed roles of women and men rather than biologically determined differences. Studies on the role of gender differences in household fuel transition frame gender as bilogical construction of male and female rather than the social responsibilities attached to it. Using data from Uganda National Household survey, this study analyzed the effect of gender differences as a social construction on household transition decisions from high to low polluting fuels and their implications on education and training in Uganda. The findings revealed that the social constructions of gender reflected in household headship and education of the household head significantly affect household fuel transition decisions. The study concludes by highlighting the implications of such social constructions on education and training in Uganda.